Upregulation of 6‐phosphofructo‐2‐kinase (PFKFB3) by hyperactivated mammalian target of rapamycin complex 1 is critical for tumor growth in tuberous sclerosis complex. Issue 5 (20th January 2020) - Wang, Yani; Tang, Sisi; Wu, Yuncui; Wan, Xiaofeng; Zhou, Meng; Li, Hongwu; Zha, Xiaojun
Abstract: Tuberous sclerosis complex (TSC) is an autosomal dominant disease characterized by the benign tumor formation in multiple organs. The main etiology of TSC is the loss‐of‐function mutation of TSC1 or TSC2 gene, which leads to aberrant activation of mammalian target of rapamycin complex 1 (mTORC1). In this research, we found a significant increase of 6‐phosphofructo‐2‐kinase/fructose‐2, 6‐biphosphatase 3 (PFKFB3) expression in Tsc1−/− and Tsc2−/− mouse embryonic fibroblasts (MEFs) compared with the control cells. Inhibition of mTORC1 led to a dramatic decrease of PFKFB3 expression, indicating PFKFB3 regulation by mTORC1. Moreover, suppression of mTORC1 inhibited the expression of PFKFB3 in rat uterine leiomyoma‐derived Tsc2‐null ELT3 cells and human tumor cells. Furthermore, we identified hypoxia‐inducible factor 1α (HIF‐1α) as a mediator transmitting the signal from mTORC1 to PFKFB3. Depletion of PFKFB3 inhibited proliferation and tumorigenicity of Tsc1‐ or Tsc2‐deficient cells. In addition, combination of rapamycin with PFK15, a PFKFB3 inhibitor, exerts a stronger inhibitory effect on cell proliferation of Tsc1‐ or Tsc2‐null MEFs than treatment with single drug. We conclude that loss of TSC1 or TSC2 led to upregulated expression of PFKFB3 through activation of mTORC1/HIF‐1α signaling pathway and co‐administration of rapamycin and PFK15 may be a promising strategy for the treatment of TSC tumors as well as other hyperactivated mTORC1‐related tumors.